The occurrence and predictive factors of sleep paralysis in university students - Lišková, Monika; Janečková, Denisa; Klůzová Kráčmarová, Lucie; Mladá, Karolína; Bušková, Jitka (Neuropsychiatric disease and treatment, 2016)
The aim of the present study was to assess the occurrence and predictive factors of sleep paralysis (SP) in Czech university students. Our sample included 606 students who had experienced at least one episode of SP. The participants completed an online battery of questionnaires involving questionnaires focused on describing their sleep habits and SP episodes, the 18-item Boundary Questionnaire (BQ-18), the Modified Tellegen Absorption Scale (MODTAS), the Dissociative Experience Scale Taxon, the Beck Depression Inventory II and the State-Trait Anxiety Inventory. The strongest predictive factor for the frequency of SP episodes was nightmares. The strongest predictive factor for the intensity of fear was dream occurrences. In our study sample, SP was more common in women than in men. Those who scored higher in BQ-18 experienced more often pleasant episodes of SP and those who scored higher in MODTAS were more likely to experience SP accompanied with hallucinations. While 62% of respondents answered that their SP was accompanied by intense fear, 16% reported that they experienced pleasant feelings during SP episodes. We suggest that not only the known rapid eye movement sleep dysregulation but also some personality variables may contribute to the characteristics of SP.
Keywords: sleep paralysis; personality boundaries; dissociation; nightmares; absorption